2012
DOI: 10.3109/13880209.2011.580351
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective activity ofCyperus alternifoliuson carbon tetrachloride–induced hepatotoxicity in rats

Abstract: (2012) Hepatoprotective activity of Cyperus alternifolius on carbon tetrachloride-induced hepatotoxicity in rats, Pharmaceutical Biology, 50:2, 155-161,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…A variety of crude plant extracts has been also reported to show hepatoprotective activity and may be useful in the treatment of various liver diseases with different etiology [54,55]. In the present study, we have demonstrated DNAprotective effects of lavender oil against two oxidative agents (H 2 O 2 and tBHP) in in vitro and ex vivo conditions, i.e.…”
Section: Discussionsupporting
confidence: 62%
“…A variety of crude plant extracts has been also reported to show hepatoprotective activity and may be useful in the treatment of various liver diseases with different etiology [54,55]. In the present study, we have demonstrated DNAprotective effects of lavender oil against two oxidative agents (H 2 O 2 and tBHP) in in vitro and ex vivo conditions, i.e.…”
Section: Discussionsupporting
confidence: 62%
“…Numerous studies have reported that intoxication with CCl 4 produce hepatic damage illustrated by increased levels of diagnostic markers such as ALT, AST ALP and bilirubin (total and direct) (Awaad et al. 2012 ; Joseph et al. 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of liver diseases is diverse; a variety of crude plant extracts has been reported to show hepatoprotective activity and may be useful in the treatment of these diseases (Awaad et al, 2012;Tatiya et al, 2012). The use of natural plant products having bioactive components promoted growing interest from pharmaceutical industries (Capecka et al, 2005).…”
Section: Discussionmentioning
confidence: 99%